Condições de trabalho e clima de segurança dos operários da construção de edificações - Maria Cristina Vieira de Cristo e Silva (2013)
This dissertation sought to reflect the applicability of the findings on safety climate, published in the scientific literature in the context of construction and to describe the relationship between working conditions and safety climate perceived by the workers, by verifying which factors of safety climate are influenced by working conditions. It was based on literature reviews of construction in Brazil and on working conditions and safety climate. We adopted an approach of working conditions that considers surrounding aspects of the task and simultaneously developing their own tasks, covering the processes and work organization. The article discusses four aspects that promote the existence of a positive safety climate: leadership, physical working conditions, preventions programs and safety training. In empirical research 195 questionnaire of working conditions and safety climate was applied in workers and semi-structured interviews in nine. We conducted descriptive analysis, ANOVA with post hoc Bonferroni and cluster analysis. The interviews were analyzed using hermeneutic analyses. The results of the working conditions questionnaire indicates that workers perceive the work as repetitive, with stressful situations and exposed to natural physical changes. Perceive themselves demanded in their professional qualification, compelled to teamwork and openness to the definition of their daily activities. Regarding safety climate, workers perceive the values and standards expected by the organization, perceive themselves involved with security, as very important the value that the company attaches to questions related to safety and, finally, that the relevant behaviors regarding safety are poorly perceived within the organization. According to the safety climate profiles defined by cluster analysis there isn´t a consolidated perception of safety climate. Relating working conditions with safety climate profiles the following factors were found as significant: Repetitive Movements, Teamwork, Lack of Support for the Implementation of Task, Social Discrimination and Sex Discrimination. The present study covered the preparation of two papers. The first focused on the review of the literature of safety climate. The second article, started with the questions raised in the first and summarized the results of an empirical research.